Goldenhar syndrome with left bronchopulmonary agenesis: A rare association - Ghimire, B; Thapa, B; Shrestha, UK; Sayami, P (Journal of Institute of Medicine Nepal, 2011)
An eleven years female presented with recurrent chest infection since childhood with markedly diminished air entry on her right chest and mediastinal shift. She also had vague facial deformity with multiple auricular appendages. Computed tomography showed collapse of the left lung and on thoracotomy, complete agenesis of the left lung was noted. Goldenhar anomaly is rare and presents with variable degree of external anomaly. Its association with bronchopulmonary agenesis is extremely rare with few cases reported in the world literature. Features of other congenital should be sought for in a child with facial asymmetry, external auditory appendages, malformation of the, nose, soft palate, lip and mandible etc so that appropriate treatment can be administered. DOI: http://dx.doi.org/10.3126/joim.v32i2.4950 Journal of Institute of Medicine, August, 2010; 32: 60-62